Abstract gringo. Issue 4 (3rd September 2015) - GEBSER, MARTIN; HARRISON, AMELIA; KAMINSKI, ROLAND; LIFSCHITZ, VLADIMIR; SCHAUB, TORSTEN
Abstract: This paper defines the syntax and semantics of the input language of the ASP groundergringo . The definition covers several constructs that were not discussed in earlier work on the semantics of that language, including intervals, pools, division of integers, aggregates with non-numeric values, and lparse-style aggregate expressions. The definition is abstract in the sense that it disregards some details related to representing programs by strings of ASCII characters. It serves as a specification forgringo from Version 4.5 on.